Sherren`s triangle hyperaesthesia a tool to rule out complicated appendicitis - Lamture, Yashwant R.; Ramteke, Harshal; Gajbhiye, Varsha (International Surgery Journal, 2018)
Background: Acute appendicitis is the most common surgical emergency. In spite of sophisticated new investigations mainstay of diagnosis depends on clinical sign and symptoms, Sherren`s triangle hyperaesthesia is very important sign with controversial efficacy about it in available literature. Hence this study was undertaken to prove its efficacy of it. Methods: This study was conducted in 418 patients with 186 females and 251 males. Patients were of acute appendicitis operated for appendicectomy included in the study. Data analysis was done by data statistic software. Results: Sensitivity and specificity of hyperaesthesia in Sherren’s triangle were 47.7% and 42.9% respectively with positive and negative predictive values were 92.1% and 5.56%. Conclusions: Hence it indicates that hyperaesthesia in Sherren’s triangle is important sign to suspect to support diagnosis of acute appendicitis. It has minimal significance to rule out it. This sign plays very important role in a diagnosis of complicated appendicitis like obstructive appendicitis.